2016
DOI: 10.1111/jpn.12511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of calf starter with fennel powder on performance, weaning age and fermentation characteristics in Holstein dairy calves

Abstract: The objective of this experiment was to investigate the effects on performance, weaning age and rumen fermentation characteristics in Holstein calves when fennel powder was added to their starter diets. Thirty Holstein calves with a mean birth weight 40 kg (SD = 0.5) were allocated randomly to one of the following experimental diets: (i) control (starter diet without fennel powder), (ii) starter diet containing 0.4% of fennel powder and (iii) starter diet containing 0.8% of fennel powder (DM basis). The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
3
20
1
Order By: Relevance
“…Conventional antibiotics, added to liquid or starter feeds, have been used to decrease the morbidity and mortality, and to increase the feed intake and growth in calves; however, the use of such antibiotics in animalagriculture has been criticized in terms of the emerging public health crisis due to antibiotic resistance (Hajalizadeh et al, 2019). Therefore, there has been growing interests in the use of herbal plants such as fennel (Foeniculum vulgare) as alternatives to conven-tional antibiotics in promoting the growth and health of young animals (Saeedi et al, 2017;Hajalizadeh et al, 2019;Kargar et al, 2021). It has also been used for prevention or treatment of the digestive and respiratory diseases (Badgujar et al, 2014;Kooti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional antibiotics, added to liquid or starter feeds, have been used to decrease the morbidity and mortality, and to increase the feed intake and growth in calves; however, the use of such antibiotics in animalagriculture has been criticized in terms of the emerging public health crisis due to antibiotic resistance (Hajalizadeh et al, 2019). Therefore, there has been growing interests in the use of herbal plants such as fennel (Foeniculum vulgare) as alternatives to conven-tional antibiotics in promoting the growth and health of young animals (Saeedi et al, 2017;Hajalizadeh et al, 2019;Kargar et al, 2021). It has also been used for prevention or treatment of the digestive and respiratory diseases (Badgujar et al, 2014;Kooti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many important enzymes also require trace minerals, which are vital for enzymatic and structural functions [12]. Therefore, fennel and dill by-products can also be used as feed additives to promote the healthy growth of animals, increase gastrointestinal (GI) peristalsis and intake, and improve intestinal microorganism balance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Such compounds give fennel strong pharmacological activities, including antibacterial, antioxidant, and hepatoprotective activities (Kooti et al, 2015;Ghazy et al, 2021). Saeedi et al (2017) stated that supplementing the starter diet of Holstein dairy calves with fennel for 2 weeks improved their growth and decreased the weaning age. Furthermore, Hajalizadeh et al (2019) observed that feeding growing lambs for 80 days on diet supplemented with fennel at 1.5% of diet increased feed intake, feed conversion, final body weight and live weight gain.…”
mentioning
confidence: 99%